2016
DOI: 10.2147/opth.s90789
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl oxidase-like 1 polymorphisms in a southwestern Greek cataract population with pseudoexfoliation syndrome

Abstract: PurposeThe aim of this study was to determine the possible association of rs1048661 and rs3825942 single nucleotide polymorphisms (SNPs) in the lysyl oxidase-like 1 (LOXL1) gene of cataract patients from southwestern Greece with pseudoexfoliation (PEX) syndrome.Patients and methodsNinety-three patients with PEX syndrome and 74 without PEX syndrome were recruited with the principal diagnosis being cataract. LOXL1 SNPs, rs1048661 and rs3825942, were genotyped by using polymerase chain reaction.ResultsThe G allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…• rs10486(G) Single Nucleotide Polymorphism was found in 47(94%) cases and 9(18%) control subjects and this difference was statistically highly significant (p = 0.001). A study conducted by Panoutsopoulos et al 18 in 2016 also found a significant association for the G allele of rs10486 with high risk of development of PXF syndrome. While, this is in contrast to a study done at Aravind eye hospital by Ramprasad et al [19] in 2007 where they did not find any significant association of PEX syndrome with rs10486 SNP.…”
Section: Discussionmentioning
confidence: 87%
“…• rs10486(G) Single Nucleotide Polymorphism was found in 47(94%) cases and 9(18%) control subjects and this difference was statistically highly significant (p = 0.001). A study conducted by Panoutsopoulos et al 18 in 2016 also found a significant association for the G allele of rs10486 with high risk of development of PXF syndrome. While, this is in contrast to a study done at Aravind eye hospital by Ramprasad et al [19] in 2007 where they did not find any significant association of PEX syndrome with rs10486 SNP.…”
Section: Discussionmentioning
confidence: 87%
“…[38] изучен материал различных тканей глаза -радужной оболочки, хрусталика, цилиарного тела -от 25 пациентов с ПЭС/ПЭГ и 25 индивидуумов из группы контроля, установлено уменьшение уровня экспрессии гена LOXL1 в тканях глаза на 20% на каждый рисковый аллель полиморфизма rs1048661. Исследования в разных популяциях показали значимые ассоциации rs1048661 гена LOXL1 с развитием ПЭС/ПЭГ [21,39,40] и ПОУГ [41]. Однако обращает на себя внимание тот факт, что в этнически разных популяциях рисковое значение для ПЭС/ПЭГ имеют различные генетические варианты rs1048661 LOXL1: 141Arg -в европейских и южноафриканских популяциях, 141Leu -в восточноазиатских.…”
Section: оригинальные статьиunclassified